Characterization of antimicrobial resistance and virulence genes in Enterococcus spp. isolated from retail meats in Alberta, Canada - Aslam, Mueen; Diarra, Moussa S.; Checkley, Sylvia; Bohaychuk, Valerie; Masson, Luke (International journal of food microbiology, 2012)
The objective of this study was to characterize antimicrobial resistance (AMR) and virulence genotypes of Enterococcus spp. particularly Enterococcus faecalis isolated from retail meats purchased (2007–2008) in Alberta, Canada. Unconditional statistical associations between AMR pheno- and genotypes and virulence genotypes were determined. A total of 532 enterococci comprising one isolate from each positive sample were analyzed for antimicrobial susceptibility. A customized enterococcal microarray was used for species identification and the detection of AMR and virulence genes. E. faecalis was found in >94% of poultry samples and in about 73% of beef and 86% of pork samples. Enterococcus faecium was not found in turkey meat and its prevalence was 2% in beef and pork and 4% in chicken samples. None of the enterococci isolates were resistant to the clinically important drugs ciprofloxacin, daptomycin, linezolid and vancomycin. Multiresistance (≥3 antimicrobials) was more common in E. faecalis (91%) isolated from chicken and turkey (91%) than those isolated from beef (14%) or pork (45%). Resistance to aminoglycosides was also noted at varying degrees. The most common resistance genes found in E. faecalis were aminoglycosides (aac, aphA3, aadE, sat4, aadA), macrolides (ermB, ermA), tetracyclines (tetM, tetL, tetO), streptogramin (vatE), bacitracin (bcrR) and lincosamide (linB). Virulence genes expressing aggregation substances (agg) and cytolysin (cylA, cylB, cylL, cylM) were found more frequently in poultry E. faecalis and were unconditionally associated with tetM, linB and bcrR resistance genes. Other virulence genes coding for adhesion (ace, efaAfs), gelatinase (gelE) were also found in the majority of E. faecalis. Significant statistical associations were found between resistance and virulence genotypes, suggesting their possible physical link on a common genetic element. This study underscores the importance of E. faecalis as a reservoir of resistance and virulence genes and their potential transfer to humans through consumption of contaminated undercooked meat. ►Enterococcus faecalis was found in >94% of poultry samples. ►Resistance to clinically important drugs was not found in any enterococci. ►Resistance genes were more commonly found in E. faecalis from poultry meats. ►Virulence genes were also found more frequently in poultry E. faecalis. ►Statistical associations were found between resistance and virulence genotypes.